Emma [videorecording (DVD)] - McGrath, Douglas; Paltrow, Gwyneth, 1972-; Collette, Toni; Cumming, Alan, 1965-; McGregor, Ewan, 1971-; Austen, Jane, 1775-1817 (Distributed by Lionsgate, 2011)
Emma brings to life Jane Austen's novel about a woman who makes it her goal to 'fix' the lives of all her friends while ignoring her own problems.